﻿The influence of non-native invertebrate species in the food web structure of two Neotropical reservoirs - Daniel Melo Rosa; Angelo Barbosa Monteiro; Lucas Del Bianco Faria; Paulo Santos Pompeu (Aquatic Invasions)
To investigate the influence of non-native aquatic invertebrate species on food web structure, we selected two reservoirs located in the Grande River (upper Paraná River basin, Brazil) with similar fish communities, different age and different taxa introductions history. We quarterly collected fish and benthonic macroinvertebrates samples in the Volta Grande and Funil reservoirs between October 2015 and August 2016. We used conventional methods of diet evaluation to assess the sampled fish and measured the availability of invertebrates (i.e. composition and density) present in the sediment samples from each reservoir. In addition, we performed a structural analysis of trophic interaction networks. Based on the data obtained, it was possible to identify that in Volta Grande most of the energy flow, between benthonic invertebrates (prey) and the fish community (predators), occurred through non-native prey species, especially Limnoperna fortunei and Macrobrachium amazonicum, while in Funil it was shared between non-native and native prey. Species loss simulations indicated that the networks did not differ substantially between random losses and losses between groups. In general, there was a decrease in the probability of occurrence of highly connected species in both reservoirs and between non-native and native species. Results showed that the new interactions among species influenced the importance of the available energy sources for the fish in the Volta Grande reservoir. The presence of non-native prey, especially M. amazonicum, may influence the interaction network structure, promoting community dependence on non-native species to ensure robustness to environmental disturbances. In the absence of pre-invasion data, the comparative study between systems with similar fish communities may provide a better understanding of the impacts caused by the introduction of non-native invertebrate prey.